Organizational Communication Strategy in Reporting Ramadan Coverage (Jelang Berbuka) and Breaking News of the Sidang Isbat For 1 Syawal 1446 H - Anisah Humairah; Titin Setiawati; Andhika Pamungkas (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Television remains in demand thanks to its broad reach, diverse programming, and creative, collaborative production teams, supported by digital transformation to maintain broadcast quality and interactivity. This study examines the communication strategies of production teams in broadcasting Ramadan news and breaking news of the Sidang Isbat (Islamic council meeting to determine the start of Ramadan), focusing on the challenges of airing religious and public-value content. The research uses a qualitative case study approach, with interviews, observation, and documentation as data collection techniques. Data was processed through condensation, presentation, and conclusion drawing. Research findings show that TVOne's communication strategy involves cross-division coordination, the development of religious-commercial content, multiplatform usage, and a deep understanding of the Ramadan audience’s characteristics to deliver accurate, relevant, peaceful, and professional information across various broadcast channels. TVOne's Sidang Isbat Breaking News emphasizes accuracy, neutrality, and intensive cross-team coordination, delivering information based on scientific and religious data, and is broadcast live with multiplatform support for broad reach. The Jelang Berbuka (Before Iftar) program combines religious and commercial content, managed by a religious team, structured with empathetic narratives, aired on TV and digital platforms, and developed through intensive coordination and audience evaluation. Conclusion: TVOne’s communication strategy emphasizes cross-division coordination, broadcast flexibility, team collaboration, digital evaluation, and the application of the 6C principles for the success of high public-value and religious programs.